Human-Computer Systems Interaction Backgrounds and Applications - Hippe, Zdzislaw S.; Kulikowski, Juliusz Lech (Advances in Intelligent and Soft Computing, 2009)
For the last decades, as the computer technology has been developing, the importance of human-computer systems interaction problems was growing. This is not only because the computer systems performance characteristics have been im-proved but also due to the growing number of computer users and of their expectations about general computer systems capabilities as universal tools for human work and life facilitation. The early technological problems of man-computer information exchange - which led to a progress in computer programming languages and input/output devices construction - have been step by step dominated by the more general ones of human interaction with-and-through computer systems, shortly denoted as H-CSI problems. The interest of scientists and of any sort specialists to the H-CSI problems is very high as it follows from an increasing number of scientific conferences and publications devoted to these topics. The present book contains selected papers concerning various aspects of H-CSI. They have been grouped into five Parts: I. General H-CSI problems (7 papers), II. Disabled persons helping and medical H-CSI applications (9 papers), III. Psychological and linguistic H-CSI aspects (9 papers), IV. Robots and training systems (8 papers), V. Various H-CSI applications (11 papers).